Biomechanical effect of inclined implants in fixed prosthesis: strain and stress analysis - Rodrigues, Vinícius Anéas (2018)
AbstractIntroductionImplant inclinations can be corrected using mini abutments at different angulations.ObjectiveTo analyze the influence of external hexagon implants in different inclinations (3 levels) on the microstrain distribution generated around three implants.MethodA geometric bone model was created through Rhinoceros CAD software (version 5.0 SR8, Mcneel North America, Seattle, WA, USA). Three implants (4.1 × 13 mm) were modeled and inserted inside the substrate at three different inclinations: 0º, 17º and 30º. Next, all groups received mini conical abutments, fixation screws and a simplified prosthesis. The final geometry was exported in STEP format to analysis software and all materials were considered homogeneous, isotropic and linearly elastic. An axial load (300N) was applied on the center of the prosthesis. An in vitro study was conducted with same conditions and groups for validating the tridimentional model.ResultStress was concentrated on the external area of the implants, in contact with the cortical bone and external hexagon. For the bone simulator, the strain increased in the peri-implant region according to the increase in the implant’s inclination. The difference between groups was significant (p = 0.000). The 30º group presented higher stress and strain concentration.ConclusionThe microstrain and stress increase around implants directly proportional to the increase of the installation angle.